Avaliação de processos extrativos para desmineralização de biomassa lignocelulósica - Giacobe, Karen (2022)
This work evaluated lignocellulosic biomass demineralization processes (sugarcane bagasse, sugarcane straw, energy cane, pine, and eucalyptus residues) using ultrasonic energy, mechanical stirring, or only mild conditions of heat for demineralization (silent condition). For scaling up the proposed protocol (12.5 and 25 g), the own bath of US was used as a reactor. After the step of demineralization, the solution was separated from the solid phase, centrifuged and the inorganics constituents (Al, Ba, Ca, Cu, Fe, K, Mg, Mn, Na, P, S, Sr e Zn) were determined for inductively coupled plasma optical emission spectrometry (ICP OES). Initially, the demineralization with the US was used as a condition cited in the literature. The proposed method was optimized with sugarcane bagasse sample. In the best operational condition (250 mg of sample, 20 mL de H2SO4 1 mol L-¹ , US bath at 25 kHz frequency, 30 min, 70% amplitude, and 50 °C) up 91% demineralization was obtained for the pool of elements (Al, Ba, Ca, Cu, Fe, K, Mg, Mn, Na, P, S, Sr, Zn). This condition was compared with mechanical stirring and in a condition in the absence of mechanical energy (silent condition), which presented demineralization efficiency of 95% and 83.7%, respectively. In the experiments with scale up (2 L of extractor solvent and 25 g of sample) the US, mechanical stirring and the silence condition presented the following demineralization efficiencies: 103.7%; 101.3% and 90.4%, respectively. These results were obtained considering the pool of all inorganic constituents of the evaluated biomasses. Additionally, a kinetic study of demineralization was carried out where it was evaluated the efficiency of demineralization at defined time intervals. This development of the lignocellulosic biomass demineralization process proved to be efficient with the use of all the proposed systems. However, with the use of the US, it was possible to promote the demineralization in shorter time intervals, less than 5 min (approximately 90%), which was not observed by other systems at the same time (less than 70%).